2016
DOI: 10.1525/mp.2016.33.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Creating Under Pressure

Abstract: A growing body of research suggests that jazz musicians concatenate stored auditory and motor patterns during improvisation. We hypothesized that this mechanism allows musicians to focus attention more flexibly during improvisation; for example, on interaction with other ensemble members. We tested this idea by analyzing the frequency of repeated melodic patterns in improvisations by artist-level pianists forced to attend to a secondary unrelated counting task. Indeed, we found that compared to their own impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It suggests that there might be an ideal CL when sight-singing. A cognitive overload could be detrimental, as other studies demonstrated (Çorlu, Maes, et al, 2015;Norgaard et al, 2016), but a load that is not sufficiently high could reflect lower engagement in the task. Consequently, this could explain how a lower load could be linked to poorer results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It suggests that there might be an ideal CL when sight-singing. A cognitive overload could be detrimental, as other studies demonstrated (Çorlu, Maes, et al, 2015;Norgaard et al, 2016), but a load that is not sufficiently high could reflect lower engagement in the task. Consequently, this could explain how a lower load could be linked to poorer results.…”
Section: Discussionmentioning
confidence: 96%
“…Cognitive load (CL) is the relationship between a task's demands and the mental resources available (Wickens & Hollands, 1999). A higher CL can hinder improvisers' creativity (Norgaard et al, 2016), instrumentalists' expressivity , and singers' timing (Çorlu, Maes, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In improvised jazz, musicians must meet the cognitive and physical constraints of performing fast and complex melodies. Having expert knowledge of common motor patterns (melodic sequences) can minimize these computational burdens [15,16,17,19,20], allowing the improviser to focus on other aspects of performance and plan more novel and interesting melodic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of chords influences jazz musicians' decisions during improvisation and their understanding of the structure of a piece (Baker, 1983;Crook, 1991;Dunscomb & Hill, 2002;Finkelman, 1997;Laughlin, 2001;Monson, 1996;Johnson-Laird, 2002;Owens, 1995;Palmer, 2016;Steedman, 1984). Although information about chords is included on lead sheets (abbreviated musical notation including the melody, lyrics and harmony of a popular song), it is believed that committing harmonic changes to memory can aid jazz musicians in making improvisations more fluid (Reeves, 2001;Spitzer, 2001Johnson-Laird, 2002Norgaard, 2011;Norgaard, Emerson, Dawn, & Fidlon, 2016;Owens, 1995) and more adaptable to different work environments (Baker, 1997).…”
Section: Jazz Musicians and Harmonymentioning
confidence: 99%
“…Awareness of chords influences jazz musicians’ decisions during improvisation and their understanding of the structure of a piece (Baker, 1983; Crook, 1991; Dunscomb & Hill, 2002; Finkelman, 1997; Johnson-Laird, 2002; Laughlin, 2001; Monson, 1996; Owens, 1995; Palmer, 2016; Steedman, 1984). Although information about chords is included on lead sheets (abbreviated musical notation including the melody, lyrics and harmony of a popular song), it is believed that committing harmonic changes to memory can aid jazz musicians in making improvisations more fluid (Johnson-Laird, 2002; Norgaard, 2011; Norgaard, Emerson, Dawn, & Fidlon, 2016; Owens, 1995; Reeves, 2001; Spitzer, 2001) and more adaptable to different work environments. Additionally, because jazz chord progressions are often modified and because jazz performers often accompany pieces they have never heard before, jazz musicians are expected to aurally identify chord patterns and their common variations when improvising with other musicians (Coker 1964, 1989; LaPorta, 2000; Laughlin, 2001; Maceli, 2009; May, 2003; Palmer, 2016).…”
Section: Jazz Musicians and Harmonymentioning
confidence: 99%